Resistivity index in the diagnosis and assessment of loss of renal function in diabetic nephropathy. (2021)
Objective: The aim of this study was to determine the haemodynamics of the intrarenal arteries from the relationship between resistivity index (RI) and kidney function, and to identify the predictors of high RI among patients with diabetic nephropathy (DN) and those with diabetes mellitus (DM) without DN. Methods: This was a cross-sectional survey of 133 participants, comprising 40 subjects with DM without DN, 53 with DM with DN and 40 healthy controls. Information obtained was demographics, lifestyle, medical and medication histories, while anthropometric and blood pressure measurements were taken. Albuminuria and estimated glomerular filtration rate were determined and RI was measured using a Doppler ultrasound scan. Results: The mean intrarenal artery RIs were higher among the patients with DM without DN (0.60 ± 0.04) and the group with DM with DN (0.61 ± 0.04) than in the controls (0.56 ± 0.04) (p = 0.02). Glycated haemoglobin (HbA1c) predicted high RI in the DM without DN group (OR 2.81; CI: 1.73–9.03) while hypertension (OR 3.60; CI: 1.06–12.22) predicted high RI in the DM with DN group. Conclusion: Elevated intrarenal artery RI was prevalent among patients with DM without DN and those with DM with DN, while elevated HbA1c level and hypertension predicted elevated RI in subjects with DM without DN and those with DM with DN.